Betaine promotes osteogenic differentiation in immortalized human dental pulp-derived cells - Chatvadee Kornsuthisopon; Dusit Nantanapiboon; Sunisa Rochanavibhata; Nunthawan Nowwarote; Worachat Namangkalakul; Thanaphum Osathanon (Nature Publishing Group, 2022)
Abstract Objectives This study aimed to evaluate the effect of betaine (BET) on immortalized human dental pulp stem cell (ihDP) osteogenic differentiation. Materials and methods hDPs were immortalized using SV40 T-antigen transfection. Characterization, multilineage differentiation, proliferation, cell cycle, colony-forming unit, and cellular senescence were evaluated (n = 4). The effect of BET on ihDP response was assessed (n = 4). Osteogenic differentiation was detected using ALP, ARS staining, and RT-qPCR (n = 4). To investigate the involvement of calcium signaling, the cells were pretreated with either 8-(NN-diethylamino)octyl-3,4,5-trimethoxybenzoate (TMB-8) or thapsigargin before BET treatment (n = 6). Results ihDPs retained similar phenotypic characteristics presented in hDPs but exhibited an increase in cell proliferation and extended culture to passage 25. An increased proportion of cells in S and G2/M phases without senescence was observed in ihDPs. BET (50 mM) treatment significantly increased mineral deposition at 14 days and upregulated ALP, MSX2, BMP2, and RUNX2 expression. TMB-8 pretreatment reduced the effect of BET-induced ihDP osteogenic differentiation, whereas thapsigargin promoted osteogenic differentiation in ihDPs synergistically with BET. Conclusion ihDPs showed superior proliferation ability and a longer life span, which could serve as a promising cell for regenerative dentistry. BET promoted odonto/osteogenic differentiation via intracellular calcium regulation.